Using Dynamic Solar Shading Devices on the Building Envelope of Government Schools to increase Thermal Performance and Improve Energy Consumption (Eurasian Journal of Engineering and Technology, 2024)
The Egyptian state seeks to develop the educational system and overcome many of the challenges it faces, according to an ambitious plan to apply to existing educational buildings, rehabilitate them and raise their efficiency, and to improve the quality of the internal environment for students, and for better education in government schools, and achieving thermal comfort for students inside classrooms is also considered. Study is one of the most important requirements for the quality of the educational process that is achieved through good design of the external envelope of the educational building, as it is the main focus of all thermal control processes and the link between the internal and external environment [1]. The research aims to show the role of Dynamic solar shading devices on the building envelope of Educational research aims to achieve thermal comfort and reduce energy consumption in school classrooms in the Greater Cairo region, as a result of the inefficiency of the existing outer shell of these schools. An applied study was conducted on a government school in the Greater Cairo region using computer simulation in the Design Builder 6.1 program to measure the effect of using Dynamic solar shading devices. In raising the thermal performance and improving energy consumption on the openings in the outer shell of the southern school classrooms, and also measuring the effect of using Dynamic solar shading devices and smart materials together on the outer shell of the southern school classrooms. The results show through application that the use of horizontal moving solar refractors and glass treated with Nano technology (Double Low-E Elec Reflective Colored glass) with a thickness of 6 mm and 13 mm air (SHGC = 0.119), (LT = 0.12), (UV = 1.616), on The outer shell of the southern school classrooms works to save energy better than using Dynamic solar shading devices only on the Building Envelope of the southern classrooms, as the energy consumption changes with the angle of the breaker, in addition to increasing the percentage of energy savings as a result of using glass treated with Dynamic solar shading